PEMETAAN POTENSI OBJEK WISATA DI PULAU AMBON (PENDEKATAN SWOT DAN IFAS EFAS) - Bin Raudha Hanoeboen (Jurnal Cita Ekonomika, 2017)
The research was conducted at Namalatu Beach, Hunimua Beach and Natsepa Beach. This study aims to map the tourism potential on Ambon Island. The data used in this study are secondary data from Time Series data from 2013 to 2015 obtained from the Maluku Provincial Tourism Office and the Central Bureau of Statistics of Maluku Province and primary data processed. The Internal Factor Evalution Matrix (IFE) is used to analyze the factors in the form of strengths and weaknesses possessed. Internal factor data is sought to analyze matters relating to several functional tourism objects. The preparation of IFAS and EFAS tables is carried out by giving a weight of 0.20 or 20% (Strong and high), 0.15 or 15% (Above average), 0.10 or 10% (Average), 0.05 or 5% (below average). And 0.00 or 0% (unaffected) with a rating scale starting from 1 (poor) to 4 (Outstanding) based on the influence of these factors Namalatu Beach Attractions, Hunimua Beach, Natsepa Beach and World Peace Gongs are then multiplied and added to get total scores from IFAS and EFAS tables. The process of weighting and granting IFAS and EFAS table ratings is based on answers to questionnaires, interviews with related parties and research observations.